2014
DOI: 10.1093/cid/ciu862
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Change in the Era of HIV Combination Antiretroviral Therapy: The Longitudinal CHARTER Study

Abstract: NC change is common in HIV infection and appears to be driven by a complex set of risk factors involving HIV disease, its treatment, and comorbid conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
296
6
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 352 publications
(323 citation statements)
references
References 27 publications
15
296
6
6
Order By: Relevance
“…This frequency of HAND is somewhat lower than the estimates for HAND in other large cohort studies that report a HAND prevalence of 47% excluding severely confounded cases. 9 Our study excluded additional potentially contributing confounders for cognitive impairment and that could account for the lower prevalence rate of HAND. Demographic differences between the MACS and CHARTER cohorts (e.g., the MACS cohort has a higher mean education and the CHARTER cohort includes both men and women) could also account for these differences.…”
Section: Activities Of Daily Living: the Macs Uses An Adaptation Ofmentioning
confidence: 99%
“…This frequency of HAND is somewhat lower than the estimates for HAND in other large cohort studies that report a HAND prevalence of 47% excluding severely confounded cases. 9 Our study excluded additional potentially contributing confounders for cognitive impairment and that could account for the lower prevalence rate of HAND. Demographic differences between the MACS and CHARTER cohorts (e.g., the MACS cohort has a higher mean education and the CHARTER cohort includes both men and women) could also account for these differences.…”
Section: Activities Of Daily Living: the Macs Uses An Adaptation Ofmentioning
confidence: 99%
“…Moreover, we recently showed that aviremic patients with ANI do not display the same pattern of immune activation than MND, suggesting that this definition is not stringent and not represent overt disease, or that it is a pre-clinical condition of more severe forms of impairment [34]. However, others have showed that patients with ANI have higher risks to deteriorate over time than unimpaired subjects [45][46][47]. Therefore, despite the ongoing debates about its real role, diagnosing ANI is one of main priorities and difficulties in the management of HAND in the cART era.…”
Section: Discussionmentioning
confidence: 99%
“…Maintain close collaboration of HIV physician with psychiatrist Table 1: Recommendations for overcoming challenges in the management of psychiatric comorbidities in HIV [32][33][34][35][36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%